Identity status and attachment in adolescents with attention deficit hyperactivity disorder - Çuhadaroğlu-Çetin, Füsun; Akdemir, Devrim; Tüzün, Zeynep; Cak, Tuna; Şenses-Dinç, Gülser; Taşğın-Çöp, Esra; Evinç, Gülin (The Turkish Journal of Pediatrics, 2013)
Identity and attachment are two concepts of different theories that might be related and that are developmentally very important in adolescence. The aim of this study was to explore the sense of identity, attachment styles and their relation in a group of adolescents with attention deficit hyperactivity disorder (ADHD). Thirty-four adolescents who were diagnosed with ADHD in childhood were reevaluated at the age of 13-16 years. The comparison group consisted of age- and gender-matched adolescents without a psychiatric disorder. The Sense of Identity Assessment Form (SIAF) and the Relationship Scales Questionnaire (RSQ) were used to examine the sense of identity and attachment styles of adolescents, respectively. Compared to adolescents without a psychiatric disorder, adolescents with ADHD, independent of the presence of a comorbid psychiatric disorder, had a similar identity formation process; however, adolescents with ADHD and a comorbid psychiatric disorder experienced more preoccupied attachment styles. Comorbid psychiatric disorders seem to be related to the insecure attachment patterns in adolescents with ADHD.